Rapid and visual identification of HIV-1 using reverse transcription loop-mediated isothermal amplification integrated with a gold nanoparticle-based lateral flow assay platform - Chen, Xu; Du, Cheng; Zhao, Qiang; Zhao, Qi; Wan, Yonghu; He, Jun; Yuan, Wei (Frontiers in Microbiology, 2023)
Human immunodeficiency virus type one (HIV-1) infection remains a major public health problem worldwide. Early diagnosis of HIV-1 is crucial to treat and control this infection effectively. Here, for the first time, we reported a novel molecular diagnostic assay called reverse transcription loop-mediated isothermal amplification combined with a visual gold nanoparticle-based lateral flow assay (RT-LAMP-AuNPs-LFA), which we devised for rapid, specific, sensitive, and visual identification of HIV-1.Here, a novel molecular diagnostic assay combining reverse transcription loop-mediated isothermal amplification (RT-LAMP) with a visual gold nanoparticle-based lateral flow biosensor (AuNPs-LFB) was created and used for the rapid, specific, and sensitive visual identification of HIV-1. The unique LAMP primers were successfully designed based on the pol gene from the major HIV-1 genotypes CRF01_AE, CRF07_BC, CRF08_BC, and subtype B, which are prevalent in China. The optimal HIV-1-RT-LAMP-AuNPs-LFBAuNPs-LFA reaction conditions were determined to be 68℃ for 35 min. The detection procedure, including crude genomic DNA RNA isolation (approximately 5 min), RT-LAMP amplification (35 min), and visual result readout (<2 min), can be completed within 45 min. Our assay has a detection limit of 20 copies per test, and we did not observe any cross-reactivity with any other bacteria pathogen in our testing. Hence, our preliminary results indicated that the HIV-1-RT-LAMP-AuNPs-LFBAuNPs-LFA assay can potentially serve as a useful point-of-care diagnostic tool for HIV-1 detection in a clinical setting.